Kajian Komparatif Penggunaan Teknologi Dikalangan Asn Milenial Dan Non Milenial Di SKPD Dinas Pendidikan Pemerintah Kabupaten Bandung Dengan Pendekatan UTAUT - Hermawan Putra, Ibnu Fauzan (Business Education Program of Universitas Pendidikan Indonesia, 2021)
Abstract : The purpose of this study was to analyze the effect of PE, EE, SI, FC on the intention to use technology in millennial and non-millennial State Civil Apparatus. To analyze the differences in technology use between millennial and non-millennial SCA with the UTAUT approach. This research was conducted at the Regional Work Unit of the Bandung Regency Education Office. This research used a survey method with a questionnaire instrument. The sampling technique used purposive sampling technique, with a total sample of 272 respondents. The data analysis technique used multiple regression analysis method. Data processing using the IBM SPSS 22 software. The results of this study are 1) PE, EE, FC have a positive and significant effect on the intention to use technology in millennial SCA, 2) SI does not have a positive and significant effect on the intention to use technology in millennial SCA. 3) PE, EE, SI, FC have a positive and significant effect on the intention to use technology for non-millennials. 4) There are differences in the use of technology between millennial and non-millennial SCA with the UTAUT approach, where PE, EE, FC, and intentions of millennial SCA are stronger than non-millennials. Meanwhile, the social influence on non-millennials is stronger than the millennial SCA.